Brotherly love and filial obedience: the commemorative programme of the Avis princes at Santa Maria da Vitória, Batalha - Farré Torras, Begoña (2014)
This dissertation focuses on a rare 15th century commemorative programme that has thus far received little scholarly attention: the collective monument erected in the Founder’s Chapel, at the Monastery of Santa Maria da Vitória, Batalha, to house the remains of four Avis princes, members of what would become known as ‘the Illustrious Generation’. A patron is proposed for the commission of this erudite monument - the princes’ eldest brother, king Duarte I - arguing its integration into a broader propaganda programme to glorify the memory of the Avis dynasty founder, king João I. The dissertation then proceeds to discuss various highly innovative features of the monument, such as its pseudo-architectural character, its use of sophisticated heraldry and personal badges, the apparent absence of religious iconography on the tombs and, importantly, the collective nature of the programme, key to its interpretation. Using a semiotic approach, a discussion is also offered on the way the various formal, iconographic and conceptual novelties of the princes’ monument impacted on the 15th century monumental landscape in Portugal. Finally, the monument and the chapel housing it are looked at through the prism of the various readings that successive generations of viewers have projected onto it, from the time of its creation to the turn of the 20th century, in order to offer a more comprehensive understanding of the object as it stands today.